2019
DOI: 10.1111/cup.13463
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleate cell angiohistiocytoma: A clinicopathologic study of 62 cases and proposed diagnostic criteria

Abstract: Background: Multinucleate cell angiohistiocytoma (MCAH) is an uncommon and likely underdiagnosed entity that is thought to be of vascular and fibrohistiocytic origin. Methods:We retrospectively reviewed all cases diagnosed as MCAH at the Yale Medicine Dermatopathology laboratory between 1 January 1990 and 1 September 2018. Sixty-two cases were retained. We performed immunohistochemistry on the ten most inflamed lesions found and assessed for a possible alteration within the Wnt/ß-catenin signaling pathway, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 17 publications
2
51
0
1
Order By: Relevance
“…Plasma cells are evidently involved in CP, but may also be occasionally increased in number, around vessels in MCAH. 10 To conclude, cutaneous plasmacytosis is a rare infiltration of the skin by plasma cells, which may have been triggered the perpetual antigenic exposure in our patient with chronic hepatitis B. We believe the MCAH-like reaction pattern in the skin specimen to have been a reactive inflammatory process brought upon by either the plasmacytic infiltrate or the chronic hepatitis B.…”
Section: Case Reportmentioning
confidence: 59%
See 4 more Smart Citations
“…Plasma cells are evidently involved in CP, but may also be occasionally increased in number, around vessels in MCAH. 10 To conclude, cutaneous plasmacytosis is a rare infiltration of the skin by plasma cells, which may have been triggered the perpetual antigenic exposure in our patient with chronic hepatitis B. We believe the MCAH-like reaction pattern in the skin specimen to have been a reactive inflammatory process brought upon by either the plasmacytic infiltrate or the chronic hepatitis B.…”
Section: Case Reportmentioning
confidence: 59%
“…In addition, the largest single‐institution review of MCAH (62 cases) had found indeed a single case in which MCAH was found to be associated with another disease (liver cirrhosis from chronic hepatitis C), yet, its clinical and histological presentation were different than the so‐called “classic MCAH.” The clinical presentation of our case was more representative of cutaneous plasmacytosis, given the brown‐purple plaques located on the axillae and groin. In contrast, MCAH usually presents as reddish‐brown papules and affects in around 50% of cases the hands or fingers . We believe MCAH may at times coexist with an associated systemic or local cutaneous disease, but that most cases arise spontaneously as a primary vascular/fibrohistiocytic process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations